Pengaruh Politik Organisasi Pada Motivasi Karir Pegawai - Titis Naniri; Humaidah Muafiqie; Abdul Adzim (Universitas Darul Ulum, 2018)
Ferris et al. (1992) suggests three political consequences in the working environment for individuals: First, leaving the organization; Second, remain a member of the organization but silent not participate in political activity, and; Third, remain a member of the organization and actively engage in political activities. Research explores the third consequence through the dynamics of career motivation. Research randomly sampled 76 civil servants from five sub-district offices in Jombang District Government. The data of career motivation measurement and perception of organizational politics were analyzed by structural equation model. The results of the analysis show that employee career motivation will increase in the perceived political environment. The research findings explained that being an active member of the organization and actively involved in political activities can be understood as increasing career identity, career insight and career resilience. The career identity in a perceived political environment can be understood as an increased work involvement and desire for upward mobility. Work involvement can be understood as increasing job involvement, professional orientation, commitment to managerial work and primacy of work. Desire for upward mobility can be understood as the increasing need for advancement, need for recognition, need to dominate, financial motivation and ability to delay satisfaction. Career insights in a perceived political environment can be understood as increasing objectives and clear paths of objectives, the flexibility of goals, the need for change, social percepptiveness, realistic expectations, career decisions, and future orientation. Career resilience in a perceived political environment can be understood as increased self-efficacy, risk-taking, and non-dependence. Self-efficacy can be understood as an increasing self-esteem, need autonomy, adaptability, internal control, achievement, initiative and creative needs. Risks taking can be understood as increasing the tendency to take risks, not afraid to fail, no need for security and tolerance of uncertainty. Dependence can be understood as a decrease in career dependence, the recognition of superiors and subordinates. Research findings prove organizational politics is functional, support for positive perspective, and counter the flow of political understanding as selfishness behavior and contrary to organizational goals.